Tidal exchanges of carbon, nitrogen and phosphorus between a Sarcocornia salt-marsh and the Kariega estuary, and the role of salt-marsh brachyura in this transfer - Taylor, David Ian (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1988)
Tidal exchanges of organic carbon, nitrogen and phosphorus between a south temperate Sarcocornia marsh and its associated estuary are examined. Subterranean water flow was small, and the hydraulic exchange between the two systems largely surficial. The dominant tidal signal was semi-diurnal, and the extent of inundation of the marsh varied considerably as a consequence of interactions of semi-lunar tidal cycles with changes in daily mean sea level. Annual net fluxes of organic carbon were directed from the marsh to the estuary, but amounted to less than 2% of marsh aerial net primary productivity. This indicates the incompatibility of E.P. Odum's outwelling hypothesis to this marsh-estuarine system. The direction of net flux of organic carbon switched on a time-scale of days. These directions were largely correlated with mesoscale oceanic events, which materially altered the extent of marsh inundation, and which provided evidence of the mutual exclusivity of outwelling of DOC from the marsh and oceanic upwelling. Laboratory mesocosm experiments using intact marsh blocks of sediment from the marsh were conducted to identify the proximate processes and interactions at the marsh-water interface responsible for the variability of marsh-estuarine exchanges. Patterns of fluxes of organic carbon, total nitrogen and phosphorus were markedly different in the structurally contrasted tidal creek and Sarcocornia Zone regions of the marsh. Both regions exported these components, but the fluxes of organic carbon and total phosphorus were significantly larger from the tidal creek than from the Sarcocornia zone, and the opposite applied to nitrogen. The presence of brachyuran crabs . the most numerous macrofauna on the marsh enhanced the flux of carbon, nitrogen and phosphorus from the marsh biocoenosis, largely as a result of the effect of their bioturbation. Evidence is examined which suggests that differential mobilization of nutrients in the two zones by crabs is responsible for biogeochemical coupling of these two regions , which may account for the elevated productivity of salt- marsh systems
Keywords: Salt marsh ecology -- South Africa -- Eastern Cape; Salt marsh animals -- South Africa -- Eastern Cape; Kariega River